Linking DNA damage and senescence to gestation period and lifespan in placental mammals - Singh, Vijay Pratap; Singh, Pushpendra (Frontiers in Cell and Developmental Biology, 2024)
The mechanism that synchronizes the timing of parturition remains a mystery. Each mammalian species has a specific duration of gestation that is determined by integrated interactions among the mother, placenta, and fetus. Senescence is primarily driven by DNA damage and is one of the critical factors influencing both parturition and lifespan. In this study, we investigated senescence as a physiological process during pregnancy and observed a gradual physiological increase in senescence in the maternal decidua and placental cells with gestation. This increase in senescence was associated with a gradual physiological increase in DNA damage during gestation. An analysis of the AnAge dataset revealed a positive correlation between the gestation period and maximum lifespan across 740 mammalian species. This finding supports the hypothesis that the rates of DNA damage and senescence may impact both the gestation period and lifespan. We suggest that the relationship between gestation period and lifespan in mammals is mediated by species-specific rates of DNA damage and senescence, necessitating further explorations into their causal roles.